STUDENT WORKSHEET DESIGN ANALYSIS BASED ON ADAPTIVE INTELLIGENCE WITH AN APPROACH OF ASSESSMENT AS LEARNING - Rukli Rukli; Muh Nur Iqramsyar (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Creativity is part of the demands of industrial revolution 4.0 mathematics learning. Worksheets practically support the cultivation of creative skills, but the existing worksheets made by teachers do not support the development of student's creative abilities. The research aims to design worksheets according to students' intelligence with an assessment as learning approach. The study uses an explorative, descriptive, evaluative approach to examine, analyze, and evaluate teacher-made student worksheets with an assessment as learning approach to obtain the work process and components of the worksheet design based on adaptive intelligence. The research subjects were students of class V and teachers of grades IV-VI. There were nine students and three teachers involved in the study. Subjects were divided into three groups. Each group consists of three students and one teacher to conduct a dialogue with an assessment as learning approach. The instrument uses an observation sheet and a fill-in sheet. Data analysis used a constructive descriptive approach. The results of the study show the following. First is the convergence of nine multiple intelligences into linguistic, spatial, and logical mathematics. Second, the core content consists of two parts, namely blocks and cubes. Third, adaptive worksheets do not focus on the material but on how to work according to students' creativity. Fourth, the exercise is part of the material learning process, not a separate component. Fifth, the results of the worksheet design are more about the process of making adaptive worksheets than the final product results. Based on these, mathematics teachers can design adaptive worksheets according to established procedures by paying attention to the core material of each material or subject and the dominance of multiple intelligences.